Protective Effects of Grape Seed Extract (GSE) against the Respiratory System following Formalin Exposure on Balb/c Mice - hasan pahang*; Bahram Bibak; Mehran Vatanchian Yazdi; Ali Shamsara (Lorestan University of Medical Sciences, 2023)
Background and Aim: As it has been reported in previous studies, the prevalence of respiratory distress is related to a variety of environmental factors. Among them, formaldehyde exposure also irritates the respiratory tract and augments the risk of airway diseases. The aims of this study was to determine the protective impacts of grape seed extract against (GSE) following formaldehyde exposure on Balb/c mice. Materials and Methods: Twenty-four adult Balb/c mice were divided into the following groups: 1-control (Ctrl) group, 2-formaldehyde exposure (FOR) group, 3-formaldehyde exposure and grape seed extract treatment (FOR+GSE) group and 4- grape seed extract treatment (GSE) group. The mice in groups 3 and 4 received 200 mg/kg GSE intraperitoneally and the mice in groups 2 and 3 were exposed to 3 mg/m3 formalin from 8 a.m. to 3 p.m., 7 h/day, 6 days/week, for 4 weeks. At the end of experimental periods, the tissue samples were removed from the trachea and the lungs and immersed in 10% formalin to be prepared for histological examination. Finally, the level of malondialdehyde (MDA) was evaluated in the plasma of the blood samples. Results and Conclusions: Data analysis showed that formaldehyde exposure could significantly reduce the weight of the mice (p<0.05). Moreover, formaldehyde caused epithelial metaplasia and edema of sub-epithelial space in the trachea. The wall of blood vessels was thickened. However, GSE consumption moderated some of formaldehyde effects. Treatment with GSE significantly reduced the MDA level p<0.05. Conclusion: GSE could reduce the marker of oxidative stress and stimulate antioxidant defenses against formaldehyde inhalation.